Risk-Informed Strategic Governance in Precast Concrete Production as A High-Risk Industry: Cross-Sector Evidence from The Construction and Oil & Gas Industries - Asyik, Noor; Latief , Rusdi Usman; Burhanuddin, Syarif (Scientific Contributions Oil and Gas, 2026)
High-risk industrial production systems, particularly in the oil and gas sector, are characterized by capital-intensive operations, strict regulatory requirements, and extremely low tolerance for technical failure. In such environments, misalignment between technical risk exposure and strategic decision-making may escalate into significant operational, financial, and safety consequences. However, empirical examination of risk-informed strategic governance in oil and gas production systems remains limited due to data accessibility and confidentiality constraints. To address this gap, this study proposes an integrated risk-informed strategic governance framework using precast concrete manufacturing in Indonesia as a representative high-risk industrial production system with structural characteristics analogous to oil and gas fabrication and EPC-based operations. This study integrates the Risk Breakdown Structure (RBS) and Risk Priority Number (RPN) methods with the Quantitative Strategic Planning Matrix (QSPM) to explicitly link quantified technical risk exposure with strategic governance priorities. A descriptive–quantitative approach was employed, involving leading precast concrete companies in Indonesia to capture actual industrial production conditions. The research was conducted through three main stages: (1) systematic identification and hierarchical classification of technical risks using the RBS method; (2) quantitative assessment and prioritization of risks using the RPN method based on severity, occurrence, and detection parameters; and (3) formulation and prioritization of strategic governance responses using the QSPM approach. The results indicate that the most critical technical risks are design drawing errors, lack of supervision over the implementation of production standards, and product non-compliance with quality requirements, as reflected by the highest RPN values. Integration of RPN outputs into the QSPM analysis identifies three governance priorities with the highest Total Attractiveness Score (TAS): implementation of effective management systems, conducting operational risk management, and reducing product deviations. These priorities demonstrate the strongest quantitative alignment between dominant technical risks and strategic governance responses. Overall, the proposed RBS–RPN–QSPM integration framework strengthens the linkage between technical risk assessment and strategic governance by explicitly transforming quantified operational risk into strategic decision variables. In practice, the framework provides a structured decision-support approach that can assist oil and gas fabrication managers in prioritizing governance interventions—such as strengthening design verification, improving production supervision, and enhancing quality compliance—based on quantified technical risk exposure. Although empirically grounded in precast concrete manufacturing, the governance logic and decision-support architecture are therefore transferable to oil and gas fabrication yards, modular construction facilities, and EPC-based production systems, where strategic choices must be explicitly aligned with technical risk exposure to enhance operational robustness, regulatory compliance, and long-term sustainability.